Confucianism and Earnings Management: Evidence from China. Issue 6 (3rd May 2022) - Yang, Liu; Li, Wanli; Li, Jiaming
ABSTRACT: Using a sample of Chinese listed firms from 2007 to 2017, this paper examines the impact of Confucianism on earnings management. We find that Confucianism is significantly negatively associated with earnings management. Further analyses suggest that the inhibitory effect of Confucianism on earnings management is more pronounced when firms have weak monitoring mechanisms such as poorer corporate governance, lower institutional ownership, and less analyst coverage. Moreover, only Confucianism has a significant restraining effect on earnings management after controlling for both Confucianism and religion. Overall, our study not only contributes to the literature on earnings management from the perspective of informal systems but also deepens our understanding of the economic consequences of Confucianism at the firm-level.